35.4k views
3 votes
Sarah solves the equation as shown.

2(x + 3) = 8
1. 2x + 6 = 8
2. 2x = 2
3. x = 1

In which step did Sarah use the distributive property?
1
2
3

User Meiswjn
by
5.9k points

2 Answers

5 votes

Answer:

Step 1

Explanation:

2(x + 3) = 8

1. 2x + 6 = 8

2. 2x = 2

3. x = 1

In step 1, she distributed the 2 to the x and 3 by multiplying them and getting 2x and 6.

User Jwinn
by
6.0k points
5 votes
1st step because 2 times x is 2x and 2 times 3 is 6
User Stevemac
by
5.9k points